Pengaruh model pembelajaran somatic, auditory, visualization, intellectually (savi) berbantuan media puzzle terhadap keterampilan menulis teks narasi peserta didik kelas iv sekolah dasar - Ida Maulida Musyarofah; Rukayah Rukayah; Septi Yulisetiani (Didaktika Dwija Indria, 2025)
This study aims to determine whether or not the application of the SAVI learning model using puzzle media has an effect on fourth grade students' writing skills in learning Indonesian language. This study is a quantitative study with a quasi-experimental design. The population of this study was elementary schools in Laweyan district. The sample was selected randomly (cluster random sampling). Data collection was done through tests and observations. The validity test according to expert judgement and the reliability test according to Cronbach Alpha were used for validation. In the preceding data analysis, a normality test and a homogeneity test were carried out. The hypothesis in this study was tested using the t-test for independent samples using the SPSS version 25 programme. The t-test results in this study were analysed using the post-test results in the experimental and control classes, which had a significance value of 0.000. Compared to the alpha coefficient value 0.000 < 0.05, this means that H0 is rejected and H1 is accepted. In addition, there is a greater difference in the average score of the experimental class compared to the control class, which is 64.41> 55.90. The results of the research analysis suggest that the SAVI learning model using puzzle media has an impact on the writing competence of fourth grade primary school students.